Simon the Jester - Locke, William John, 1863-1930 (Salt Lake City, UT : Project Gutenberg, 2006)
"Simon the Jester" by William John Locke is a novel likely written in the early 20th century. The story centers around Simon de Gex, an M.P. who seeks solitude in the desolate seaside town of Murglebed-on-Sea after receiving a terminal diagnosis. As he grapples with his impending demise, Simon reflects on his life, love, and the ambitions he is leaving behind, all while bringing humor and a contemplative attitude to his misfortunes. The beginning of the novel introduces Simon as he arrives in the bleak coastal town, seeking peace and distance from the hustle of political life. In his conversations with Renniker, a knowledgeable friend, Simon humorously inquires about the most dismal place in England, leading him to Murglebed, which he describes in vividly dismal terms. Through his eyes, we see a man confronting existential questions and exploring ideas of mortality and meaning. He reveals his engagement to Eleanor Faversham, who he admires but feels he cannot marry due to his illness. The opening sets a tone of sharp wit and introspection as Simon embarks on a journey of self-discovery amidst the gloom, intending to find joy and purpose in his remaining time. (This is an automatically generated summary.)
Release date is 2006-04-13
Produced by Dagny; John Bickers; David Widger
Keywords: Fiction; Wit and humor